2011
DOI: 10.1371/journal.pntd.0001302
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Factor H Binding Proteins in Epidemic Strains from Africa: Implications for Vaccine Development

Abstract: BackgroundFactor H binding protein (fHbp) is an important antigen for vaccines against meningococcal serogroup B disease. The protein binds human factor H (fH), which enables the bacteria to resist serum bactericidal activity. Little is known about the vaccine-potential of fHbp for control of meningococcal epidemics in Africa, which typically are caused by non-group B strains.Methodology/Principal FindingsWe investigated genes encoding fHbp in 106 serogroup A, W-135 and X case isolates from 17 African countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 74 publications
3
73
1
Order By: Relevance
“…For example, isolated epidemic strains from serogroups A, W, and X (a recently identified cause of IMD in Africa, for which no vaccine exists), express fHbp proteins that share significant sequence homology with the fHbp antigen used in the 4CMenB vaccine and, therefore, may be susceptible to the bactericidal activity of 4CMenB-induced antibodies. 28,29 Indeed, results of an analysis of the bactericidal activity of sera from 4CMenB-vaccinated individuals against a panel of serogroup X epidemic strains indicated that 4CMenB may indeed confer protection against strains of this serogroup, and that this protection is likely attributable to fHbp-specific antibody responses. 30 While 4CMenB coverage of non-serogroup B strains has not been studied extensively, the susceptibility of any meningococcal strain to bactericidal antibodies elicited by 4CMenB is dependent upon both the degree of similarity between vaccine antigens and the respective target proteins, as well as the expression level of the target proteins, in each strain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, isolated epidemic strains from serogroups A, W, and X (a recently identified cause of IMD in Africa, for which no vaccine exists), express fHbp proteins that share significant sequence homology with the fHbp antigen used in the 4CMenB vaccine and, therefore, may be susceptible to the bactericidal activity of 4CMenB-induced antibodies. 28,29 Indeed, results of an analysis of the bactericidal activity of sera from 4CMenB-vaccinated individuals against a panel of serogroup X epidemic strains indicated that 4CMenB may indeed confer protection against strains of this serogroup, and that this protection is likely attributable to fHbp-specific antibody responses. 30 While 4CMenB coverage of non-serogroup B strains has not been studied extensively, the susceptibility of any meningococcal strain to bactericidal antibodies elicited by 4CMenB is dependent upon both the degree of similarity between vaccine antigens and the respective target proteins, as well as the expression level of the target proteins, in each strain.…”
Section: Discussionmentioning
confidence: 99%
“…We chose FHbp ID 22, as this sequence variant was prevalent in invasive isolates from Africa (14,20) and the immunogenicity of vaccines containing FHbp ID 22 previously had been tested in mice (6,14,16,21). The L130R substitution increased the T m of the N-terminal domain by 7.7°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FHbp sequence variants in variant group 2 are prevalent among invasive strains in Europe (12) and North America (ID 19) (13) and Africa (ID 22) (14). These two sequence variants were reported to have low thermal stability for the amino-(N-) terminal domain (15,16), whereas FHbp from variant groups 1 and 3 had high thermal stability (15,17,18).…”
mentioning
confidence: 99%
“…Issues to be studied more carefully are duration of protection in various age groups, mucosal immunity and herd protection. Of particular note, a substantial difference in immunogenicity has been observed with recombinant fHbp versus the experimental formulations of native OMV vaccines where fHbp has been included as over-expressed vaccine antigen (NOMV-OEfHbp with 3-6 times the ordinary level found in wild type strains) [89][90][91]. The total amount of fHbp in the two formulations can be more than 100 times different, and the NOMV formulation induces better anti-fHbp immunity than the recombinant vaccine.…”
Section: Vaccines Against Meningococcal Disease; Status and Perspectivesmentioning
confidence: 99%
“…Instead the vaccine can be made tolerable for humans with genetic manipulation of LPS (lpx1-mutants) [89]. Preclinical studies with NOMV vaccines have shown higher protective titres and broader immune responses, resulting in better capacity to kill strains with fHbp variants that are substantially different from the vaccine antigen selected for the vaccine [91,[93][94][95]. These observations served as inspiration for further studies of the OMV-concept and use of NOMV as a "platform" for various other antigens.…”
Section: Vaccines Against Meningococcal Disease; Status and Perspectivesmentioning
confidence: 99%